Online Self-testable Multi-core System using Dynamic Partial Reconfiguration of FPGA - G. Prasad Acharya; M. Asha Rani (International Journal of Reconfigurable and Embedded Systems (IJRES), 2017)
This paper presents a novel and efficient method of designing an online self-testable multi-core system. Testing of a Core Under Test (CoUT) in a massively multi-core system can be carried out while the system is operational, by assigning the functionality of the CoUT to one of the non-functioning/idle and pre-tested core. The methodology presented in this paper has been implemented taking a test setup by demonstrating the Dynamic Partial Reconfiguration (DPR) feature of latest FPGAs on Zynq-7 XC702 evaluation board. The simulation results obtained from the experimental setup show that the utilization of a multi-core system can be significantly improved by effectively utilizing the idle core(s) to back up CoUT(s) for on-line test without a significant hardware overhead and test latency.